The end of the perfect ten the making and breaking of gymnastics' top score --from Nadia to now - Meyers, Dvora (Touchstone, 2017)
"An exciting and insightful account of the controversial world of gymnastics, the recent changes of the scoring system, and why those changes will drive American gymnasts to the top of the sport in the twenty-first century. It was the team finals of women s gymnastics in the 2012 London Olympics and McKayla Maroney was on top of her game. The sixteen-year-old US gymnast was performing arguably the best vault of all time, launching herself unimaginably high into the air and sticking a flawless landing. But when her score came, many were baffled: 16.233. Three tenths of a point in deductions stood between her and a perfect score. But if that vault wasn t perfection, what was? For years, gymnastics was scored on a 10.0 scale. During this era, more than 100 perfect scores were awarded in major international competitions. But when the 10.0 scoring system caused major judging controversies at the 2004 Olympics, international elite gymnastics made the switch to the open-ended scoring system it uses today, making perfect scores a thing of the past and forever altering the sport in the process. Gymnastics insider Dvora Meyers examines the evolution of elite women s gymnastics over the last few decades. With insight, flair, and a boundless love for the sport, Meyers answers questions that gymnastics fans have been asking since the last perfect score was handed out over twenty years ago. She reveals why successful female gymnasts are older and more athletic than they have ever been before, how the United States became a gymnastics powerhouse, and what the future of gymnastics will hold. Bolstered by dozens of exclusive interviews with professionals representing every aspect of the sport, "The End of the Perfect 10" explores a crucial change in one of the most popular Olympic sports, and is a captivating account of elite gymnastics entry into the uncharted world of imperfection."